Banded regular/anomalous eutectic in rapidly solidified Co-61.8 at.% Si. (15th July 2019) - Fiore, Gianluca; Quaglia, Alice; Battezzati, Livio
Abstract: A novel banded microstructure consisting of regular/anomalous eutectic has been found in hypoeutectic Co-61.8at%Si rapidly solidified by either copper mould casting and melt spinning. The bands originate because of varied undercooling and growth rate in the direction of heat flow towards the copper sinks. Diffusional effects (i. e. rejection of solute) in the presence of limited convection cause fluctuations in growth rates for which the role of recalescence is highlighted. Occasional primary phase/eutectic transitions were also found. The microstructures are contrasted with those seen in furnace cooled samples where diffusion fully occurred in a quiescent melt. Graphical abstract: Unlabelled Image